The Question of the Primary Electron Acceptor in Bacterial Photosynthesis - Loach, P. A. (1972)
An electrophoretic purification of Rhodospirillum rubrum photoreceptor subunits prepared by alkaline urea-detergent disruption is described. Completely active photoreceptor subunits with less than 0.30 eq of iron (or any other transition metal) per phototrap can routinely be prepared. A new photoproduced electron paramagnetic resonance (EPR) signal has been detected in these preparations; it was shown to be due to a photoreduced species. It has a g-value of 2.0050 ± 0.0003, a peak-peak width of 7.0 ± 0.3 G, and a nearly Gaussian shape. The response of the new signal to microwave power is different from that of the EPR signal of the photoproduced primary electron donor of chromatophores. Quantum yield measurements of spin production show that the new signal is very efficiently formed (ϕ = 0.6) simultaneously with the electron donor radical. No hyperfine structure (down to 0.1 G modulation amplitude) was observed in the new signal, either at room temperature or at the temperature of liquid nitrogen. The possible identity of this molecule is discussed.